Spatio-temporal changes in the heatwaves and coldwaves in Spain (1950-2018): influence of the East Atlantic pattern - Espín-Sánchez, David; Conesa-García, Carmelo (Geographica Pannonica, 2021)
The Iberian Peninsula has a complex orography, which determines an important altitudinal gradient and alternation of valleys and mountains, and periodic cold/warm advections air. In the present investigation the evolution of the characteristics of heatwaves (HWs) and coldwaves (CWs) (number of events, frequency, duration, magnitude, and amplitude) was analyzed. A total of 28 homogeneous-period weather stations (1950-2018), grouped into six regions (cluster). After submitting the meteorological series to a process of homogenization and data quality control, various ET-SCI indices were estimated in order to obtain evolution trends in each climatic region. In all cases, there was an increase, often significant, in the recurrence of HW events (0.3 / 10 yrs) as well as a decrease in CW events (-0.2 / 10 yrs). In addition, the evolution of the above indices and anomalies was correlated with the evolution of the global index of the East Atlantic (EAi).
Keywords: Iberian Peninsula; cluster; advection; indices; teleconnection; East Atlantic